Analyse comparative de la localisation géographique des hubs de Paris et Dubaï à travers les flux aériens internationaux - Julien Lebel (M@ppemonde)
The emirates of Dubai, Abu Dhabi and Qatar are implementing ambitious, air transport strategies. Major air carriers have been established – such as Emirates Airline (1985), Qatar Airways (1994), but also Etihad Airways (2003) – and are out-competing airlines operating from other regions, like Europe and Eastern Asia. Does the geographical location of these Gulf hubs represent a real advantage, which could explain the success of locally based airlines?